VARIABILITY IN EXPRESSION OF MALE FERTILITY IN TRITICALE (XTRITICOSECALE WITTMACK) WITH TRITICUM TIMOPHEEVI CYTOPLASM. - Góral, Halina; Tyrka, Mirosław; Stojałowski, Stefan; Wędzony, Maria (Plant Breeding and Seed Science, 2009)
We present a reliable, visual method for evaluation of the level of male fertility during flowering, that is indispensable for breeding of hybrid cultivars of winter triticale based on the cms-T.timopheevi system. Detailed observations of anther development were performed on 20 F2 and BC1 plants derived from crosses between male-sterile and fertility restoring lines. Variation of anther development within florets, spikelets, spikes, and among spikes of the same plant was examined...